Inventaris en voorstellen tot beheer van het Boekenbergpark - Stryckers, Paul; Stryckers, Jan; Slembrouck, Juul; Van Hoof, A. (Deurne: [s.n.], 1973)
"Jan Stryckers, Paul Stryckers, Juul Slembrouck, A. Van Hoof"